Analisis kemampuan berpikir kritis pada materi cerita operasi hitung campuran dalam pembelajaran matematika kelas III sekolah dasar - Hasna Rezkya Salma; Riyadi Riyadi; Siti Wahyuningsih (Universitas Sebelas Maret, 2025)
Abstract. This study aims to describe students' critical thinking skills on the material of mixed arithmetic operations of addition with subtraction and multiplication with division of grade III students of SD Negeri Pajang IV Surakarta. This study is a qualitative study with a case study method. The data source in this study came from III SD Negeri Pajang IV Surakarta. The sampling technique was carried out by purposive sampling by taking 15 subjects for the analysis of test results and 4 students for the analysis of interview results. Data collection techniques used include tests, interviews, and documentation. The data validity technique uses the triangulation technique. The data analysis technique used in this study uses the Miles and Huberman approach. The results of this study indicate that students' critical thinking skills on the material of mixed arithmetic operations of multiplication and division are in the low category and the medium category for mixed arithmetic operations of addition and subtraction. It is hoped that the research results can make a positive contribution in developing more effective mathematics learning methods, as well as improving students' critical thinking skills to face increasingly complex future challenges in this digital era.Keywords: critical thinking, mathematics story problems, mixed arithmetic operations, mathematics education, and elementary school